The Effect of Physical Activity on Patients with Chronic Obstructive Pulmonary Disease (COPD) - Jankunec, Marija; Šerėnaitė, Ugnė; Lukoševičiūtė, Sonata; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2023)
Chronic obstructive pulmonary disease (COPD) is characterized by narrowing of the respiratory tract. Deterioration of pulmonary ventilation occurs, as a result of which tissues and organs are insufficiently supplied with oxygen.The aim. To review scientific literature sources and provide data on the impact of physical activity on patients with chronic obstructive pulmonary disease (COPD).The research method. The review covered scientific literature sources from the period between 2009 and 2021. Electronic scientific literature search was carried out on PubMed, Google Scholar, Cochrane Database Syst. Rev., using keywords and their combinations. Full-text and freely accessible English-language articles were included. A total of 18 literature sources were considered appropriate.The results and conclusions. COPD is characterized by coughing, shortness of breath, sputum production, and changes in blood gases. The effect of gas (stimulus) damages lung tissue. Low tolerance to physical exertion significantly complicates respiratory function. COPD is a progressive disease. One of the main COPD stimuli is shortness of breath, which restricts daily physical activity and may have a decisive impact on disability development. Age, behavioural risk factors, emphysema, chronic obstructive bronchitis, and metabolic syndromes are predisposing risk factors for COPD. As the disease progresses, physical activity decreases. Passive physical activity manifests itself in symptoms of shortness of breath and fatigue.